PENGENDALIAN MUTU TENAGA PENDIDIK BIDANG PENDIDIKAN DASAR DINAS PENDIDIKAN KABUPATEN KUTAI TIMUR - Agus Kusmawati, Maskan, dan Wesley Liano Hutasoit (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2020)
Quality control of educators or teachers in the field of basic education is avery important field in developing education in a country. Developedcountries can be sure to have an excellent system and quality of education.This is because the education sector is very influential on the quality ofhuman resources.The purpose of this study was to determine the quality of educators in thefield of basic education at the Education Office in East Kutai District and todetermine the quality control of educators in the field of basic education atthe Education Office in East Kutai District.The research method used in this study is a descriptive research method witha qualitative approach. This type of research focuses on problems or actualphenomena at the time the research is conducted, then describes the factsabout the problem being investigated as they are accompanied by rationaland accurate interpretations.The quality of education cannot be separated from the procedure ofeducational evaluation. This means that in order to improve the quality ofeducation a better evaluation system must be created. The evaluation system(measurement, testing / evaluation, evaluation and evaluation), in addition tothe procedures that must be systematic, the implementation must also havehigh accountability, and the results are expected to get recognition fromeducation stakeholders.Management of educators and education staff is a process of managingpotential human resources and has a role in realizing national educationgoals. Management of educators and education staff is a managementmechanism that must be carried out thoroughly and continuously from theteaching staff and excellence through the process of human resource planning, recruitment, selection, placement, compensation, awards,coaching and training / development, and dismissal. All of that carried out toform and produce qualified educators and education staff in accordancewith their respective fields. An educational organization such as a schoolhas the right to choose and make a selection to receive teaching staff and itseducation. This is intended so that schools can be better quality so that thestudents can be of good quality as inputs.